A population based survey of the prevalence and types of glaucoma in rural West Bengal: the West Bengal Glaucoma Study - Raychaudhuri, A (Copyright 2005 British Journal of Ophthalmology, 2005)
Aim: To determine (i) the prevalence of glaucoma in people aged ⩾50 years, (ii) the proportions of different types of glaucoma, (iii) the distributions of intraocular pressure and vertical cup disc ratio. Method: Population based prevalence survey in rural West Bengal. People aged ⩾50 years in randomly selected villages in 24 Parganas South district. The main outcome measures were diagnosis of glaucoma, based on criteria described by the International Society for Geographic and Epidemiological Ophthalmology. Results: 1594 people aged ⩾50 years were enumerated in nine villages; 1324 (83.1%) were surveyed and 1269 people adequately examined. 42 definite cases of glaucoma were identified, with prevalence increasing from 2.7% (95% CI 1.7 to 3.7) in people aged 50–59 years to 6.5% (95% CI 0.0 to 14.1) in those aged ⩾80 years. The age standardised estimate for the prevalence of all glaucoma in people aged ⩾50 years was 3.4%. Only three cases of primary angle closure glaucoma (PACG) were identified, giving a crude ratio of primary open angle glaucoma (POAG) to PACG of more than 10:1. Three people with glaucoma were blind in one eye but none was blind in both eyes. Conclusion: Compared to other surveys of glaucoma in India, the age standardised prevalence observed was less than in Hyderabad, but similar to Tamil Nadu and Dhaka. The ratio of POAG to PACG was much higher than found previously, suggesting that PACG may be less prevalent in Bengalis than in Indian populations living in south India. The authors conclude that ophthalmic services in West Bengal should focus on detecting POAG. Since there is still no satisfactory method of screening for POAG, there is no alternative to case detection (opportunistic screening) in eye clinics.